Persepsi Pemuda terhadap Peranan Karang Taruna dalam Penanganan Masalah Sosial - Annisa Yulia Handayani; Ninuk Purnaningsih; Ma'mun Sarma (Jurnal Penyuluhan, 2015)
The government should work with the elements of society to solve a growing social problem, including organizations that exist at the village level. Karang Taruna as one of the youth organizations, is a partner that could take the role in solving social problems. The purpose of this study is to determine how youth perceptions of the Karang Taruna role and the factors that influence these perceptions. Descriptive analytical study design by incidental sampling techniques to 93 youths carried out at Bogor City. Data collection was conducted between February until April 2014. Processed data using regression analysis. The results showed that age, education, motivation, experience, interaction with organization, social environment, knowledge about the social problem and knowledge about karang taruna role in the implementation of social welfare influence statistically significant to youth perceptions about Karang Taruna’s role in solving social problems.Keywords: role, karang taruna, perception, social problems, karang taruna